Kidney Dysfunction Impact on White Matter Hyperintensity Volume in Neurologically Healthy Adults - Kim, Sang Hyuck (Sci Rep, 2019)
The detrimental outcomes of white matter hyperintensity (WMH) are known to be proportional to WMH volume. This study aimed to evaluate the association between kidney dysfunction and white matter hyperintensity (WMH) volume. A total of 2,203 subjects who underwent brain magnetic resonance imaging (MRI) as part of a screening health check-up was included in this study. WMH was defined as hyperintensity signals without cavity formation in the white matter on fluid-attenuated inversion recovery images. WMH volume was measured quantitatively, and data were normalized by square root transformation prior to analysis. Mean age of the subjects was 56.9 years and mean WMH volume was 2.7 cm(3). Mean estimated glomerular filtration rate (eGFR) level was 78.0 ml/min/1.73 m(2), and 172 subjects (7.8%) were diagnosed with moderate-to-severe kidney dysfunction (eGFR < 60). Mean Urine albumin-to-creatinine ratio (UACR) was 0.02, and 166 subjects showed significant albuminuria (UACR ≥ 0.03). Multivariate analyses showed that each of UACR, significant albuminuria, and moderate-to-severe kidney dysfunction was significantly associated with increased WMH volume (all p < 0.05). When we considered significant albuminuria and moderate-to-severe kidney dysfunction simultaneously, subjects with both significant albuminuria and moderate-to-severe kidney dysfunction had more than twice the WMH volume as did those in the other groups (all p < 0.05). Kidney dysfunction, defined by albuminuria and eGFR, was independently associated with WMH volume. Risk factors related to WMH and its detrimental outcomes should be strictly modified in subjects with kidney dysfunction, especially in those with both albuminuria and a reduced eGFR.